"Culture eats strategy for breakfast": An in‐depth examination of police officer perceptions of body‐worn camera implementation and their relationship to policy, supervision, and training. Issue 3 (25th May 2022) - Willis, James J.
Abstract: Research Summary: This study uses interviews with 23 police officers from a small police department to conduct an in‐depth examination of their perceptions of three critical but understudied areas related to body‐worn camera programs: the implementation and policy‐making process, supervision, and training. The focus is on understanding the factors which contribute to, or undermine, body‐worn camera integration and acceptance. Policy Implications: Including patrol officers directly in the implementation and policy‐making processes might help increase officer acceptance of body‐worn cameras (BWCs), and the identification of potential implementation problems (especially around BWC activation, civilian notification, and minor violations of department policies). Moreover, police departments may need to anticipate resistance from features of the traditional police culture toward certain BWC uses and consider how these might be overcome. One suggestion is to conduct regular reviews of BWC footage with officers as a learning tool to help guide discretion on BWC use (especially around recording protocols), to help reframe BWCs as an innovative technology for improving street‐level performance, and to provide routine reminders to officers of the importance of BWC activation and civilian notification for achieving their potential benefits.